Acidithiobacillus ferrivorans SS3 presents little RNA transcript response related to cold stress during growth at 8 A degrees C suggesting it is a eurypsychrophile - Christel, S.; Fridlund, J.; Watkin, Elizabeth; Dopson, M. (2016)
Acidithiobacillus ferrivorans is an acidophilic bacterium that represents a substantial proportion of the microbial community in a low temperature mining waste stream. Due to its ability to grow at temperatures below 15 °C, it has previously been classified as ‘psychrotolerant’. Low temperature-adapted microorganisms have strategies to grow at cold temperatures such as the production of cold acclimation proteins, DEAD/DEAH box helicases, and compatible solutes plus increasing their cellular membrane fluidity. However, little is known about At. ferrivorans adaptation strategies employed during culture at its temperature extremes. In this study, we report the transcriptomic response of At. ferrivorans SS3 to culture at 8 °C compared to 20 °C. Analysis revealed 373 differentially expressed genes of which, the majority were of unknown function. Only few changes in transcript counts of genes previously described to be cold adaptation genes were detected. Instead, cells cultured at cold (8 °C) altered the expression of a wide range of genes ascribed to functions in transcription, translation, and energy production. It is, therefore, suggested that a temperature of 8 °C imposed little cold stress on At. ferrivorans, underlining its adaptation to growth in the cold as well as suggesting it should be classified as a ‘eurypsychrophile’.